THE IMPORTANCE AND FORMS OF ORGANIZATION OF PRIMARY EDUCATION TEACHERS’ USE OF THE PROJECT METHOD IN THE FORMATION OF STUDENTS’ LEARNING ACTIVITIES - Iqboloy Boltayeva; Zaynab Abdunazarova (Academia Science Repository, 2023)
This article is intended for teachers of primary education and provides a broad overview of the use of the project method in teaching mother tongue and reading literacy.